Application of Good Manufacturing Practices (GMP) in Frozen Squid company, PT Starfood Lamongan, East Java - Agil Putra Bimantara; Juni Triastuti (Journal of Marine and Coastal Science, 2018)
Freezing is one of processing of fishery products intended to preserve food by inhibiting the growth of microorganisms, resist chemical reactions and enzyme activity. Program eligibility freezing base in the industry is needed to ensure food safety, namely sanitation standard operating procedures (Sanitation Standard Operating Procedures / SSOP) and the good food production (Good Manufacturing Practices / GMP). Good Manufacturing Practices (GMP) are the basic requirements that should be met by a company that wants to produce quality and safe food consistently. These requirements include the production requirements, locations, buildings and facilities, production equipment and employees. Research implementation goals are to know directly how the application of GMP, knowing the factors that affect the application of GMP, know and understand the problems or obstacles that arise in the implementation of GMP in the freezing squid (Loligo vulgaris). The research was carried out at PT. Starfood International, located in Kandang Semangkon village, District Paciran, Lamongan, East Java Province on 18th January to 18th February, 2016. The work method was implemented as the descriptive method with collecting data through observation, documentation, interview, and active participation. PT. Starfood International is a branch of PT. Kelola Mina Laut which is a national private company that is form of limited company engages in the processing of fishery products. This company has three operational activity units including surimi managing unit, frozen fish managing unit and fish meal managing unit. The implementation of GMP is done by assessing some aspects include plant location, the building, the final product, processing equipment, production materials, personal hygiene, process control processing, sanitation facilities, label, product description, storage, maintenance of treatment facilities and sanitation activities, laboratory, packaging and transportation.